Inequalities of quality of life in unemployed young adults: A population-based questionnaire study - Edén Lena; Andersson Ingemar H; Axelsson Lars; Ejlertsson Göran (BMC, 2007)
Abstract Background It is well known that unemployment is a great problem both to the exposed individual and to the whole society. Unemployment is reported as more common among young people compared to the general level of unemployment. Inequity in health status and life-satisfaction is related to unemployment. The purpose of this population-based study was to describe QOL among unemployed young people compared to those who are not unemployed, and to analyse variables related to QOL for the respective groups. Methods The sample consisted of 264 young unemployed individuals and 528 working or studying individuals as a reference group. They all received a questionnaire about civil status, educational level, immigration, employment status, self-reported health, self-esteem, social support, social network, spare time, dwelling, economy and personal characteristics. The response rate was 72%. The significance of differences between proportions was tested by Fisher's exact test or by χ2 test. Multivariate analysis was carried out by means of a logistic regression model. Results Our results balance the predominant picture of youth unemployment as a principally negative experience. Although the unemployed reported lower levels of QOL than the reference group, a majority of unemployed young adults reported good QOL, and 24% even experienced higher QOL after being unemployed. Positive QOL related not only to good health, but also to high self-esteem, satisfaction with spare time and broad latitude for decision-making. Conclusion Even if QOL is good among a majority of unemployed young adults, inequalities in QOL were demonstrated. To create more equity in health, individuals who report reduced subjective health, especially anxiety need extra attention and support. Efforts should aim at empowering unemployed young adults by identifying their concerns and resources, and by creating individual programmes in relation not only to education and work, but also to personal development.